Race, sexualité, et luttes de véridiction : la racialisation dans les représentations cinématographiques de la « tournante » - Claire Cosquer (Genre, Sexualité et Société)
This paper intends to analyze three movies (La Squale, La Journée de la jupe, Sheitan), which deal mainly with, or simply mention, “tournantes”. The French term “tournantes” surfaced in the early 2000s, and refers to group rapes committed in suburbian areas. The purpose of this paper is to investigate the dovetailing of sexuality and race discourses in the constitution of “tournantes” as a problem. We identify three axes of problematization: a documentary one, a moral and political one, and an oppositional one. “Tournantes”, which generate political conflictuality, problematize race through sex without resorting only to othering and stigmatizing: they also appear to be the place of whiteness production. In particular, these representations take competing stances towards the “truth” of sex and race, suggesting that racialization can be understood as a struggle for verediction.